2019
DOI: 10.1108/bepam-11-2018-0142
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the feasibility of blockchain technology as an infrastructure for improving built asset sustainability

Abstract: Purpose The purpose of this paper is to show the feasibility of blockchain technology to perform as an infrastructure for improving built asset sustainability by providing all the necessary information for better decision making at all the stages of its life cycle. Design/methodology/approach Blockchain technology can be used as a tool to build a reliable and secure decentralized information system to capture and disseminate all the data required for different sustainability assessment models. A model is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 23 publications
0
37
0
2
Order By: Relevance
“…In such systems, utilities and smart homes in the city move from passively consuming energy and receiving demand-response calls to actively trading energy and ancillary services on blockchain and even to developing locally efficient market clearing prices (Qi and Shen 2019 ). The use of blockchain-based P2P energy transaction is able to establish sustainable energy ecosystem between prosumers, customers, and existing energy suppliers (Shojaei et al 2019 ). Finally, the keyword "Smart Home" is indicative of blockchain’s potential to monitor its resources, ensure security and privacy, and increase home automation (Li et al 2019 ).…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…In such systems, utilities and smart homes in the city move from passively consuming energy and receiving demand-response calls to actively trading energy and ancillary services on blockchain and even to developing locally efficient market clearing prices (Qi and Shen 2019 ). The use of blockchain-based P2P energy transaction is able to establish sustainable energy ecosystem between prosumers, customers, and existing energy suppliers (Shojaei et al 2019 ). Finally, the keyword "Smart Home" is indicative of blockchain’s potential to monitor its resources, ensure security and privacy, and increase home automation (Li et al 2019 ).…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…Studies have also demonstrated that AI may inhibit the achievement of 35% of SDG targets [18]. Third, blockchain can revolutionize knowledge and value of the whole life cycle of SID [22,27]. Blockchain technology is characterized in transparency, decentralization, openness, interconnection and sharing for more reliable and efficient life cycle assessment of SID [16,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Third, blockchain can revolutionize knowledge and value of the whole life cycle of SID [22,27]. Blockchain technology is characterized in transparency, decentralization, openness, interconnection and sharing for more reliable and efficient life cycle assessment of SID [16,27,28]. The last but not least category of technologies for SID is the Earth observation technology, such as remote sensing [29,30], light detection and ranging (LiDAR) [31,32], unmanned aerial vehicle (UAV) [33] and precise in-situ or ground observations [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…A tecnologia de registro Blockchain (ou sua sigla em inglês BT, Blockchain tecnology) apresenta-se como tema de grande relevância para pesquisas na área, observando seu potencial para resolução dos problemas fortemente associados à CSC. Vários autores têm destacado o potencial desta tecnologia para transformar a indústria da construção, em especial para a gestão de suprimentos [7] [8] [9].…”
Section: Introductionunclassified